The Political Law of Regulating the National Sharia Council of the Indonesian Ulema Council in the Implementation of Islamic Finance in Indonesia - Pofrizal Pofrizal; Sukamto Satoto; Hartati Hartati (Jurnal Syntax Transformation, 2025)
This research discusses the regulation of Islamic finance in Indonesia, focusing on the role of the National Shariah Council of the Indonesian Ulema Council (DSN MUI) in the context of evolving legal policies. The main objective of this research is to analyze the government's legal policy towards the DSN MUI and its impact on Islamic finance in Indonesia, as well as to provide recommendations for regulatory improvements. This research uses a qualitative approach with in-depth analysis of relevant laws and regulations, interviews with stakeholders, and review of relevant literature. The findings show that the existing regulations still face challenges in terms of legal certainty and institutional governance. The establishment of OJK Regulation No. 2 Year 2024 provides new certainty for the relationship between DSN MUI and Sharia Supervisory Board, although the position of DSN MUI is still not entirely clear. This study concludes that a change in the government's legal policy direction is needed to strengthen the position of DSN MUI and improve its integration with Islamic financial institutions in order to support the sustainable development of the Islamic economy in Indonesia.